THE UTILIZATION OF INTERACTIVE MULTIMEDIA AS A PHYSICS LEARNING MEDIA - Yeni, Dede (Journal of Higher Education and Academic Advancement, 2025)
Objective:  The purpose of this study is to: (1) investigate the use of interactive multimedia as a medium for physics learning, (2) investigate interactive multimedia models that can be applied in physics learning. Method: This research used a qualitative method with a literature approach. Results: The use of interactive multimedia in physics learning can help to illustrate physical phenomena clearly or visually, making them easier to observe and understand. Therefore, various limitations and difficulties in learning are expected to be overcome by using interactive multimedia. Novelty: To address this, the use of Information and Communication Technology (ICT)-based learning media in the form of virtual media or interactive multimedia is considered quite helpful in understanding both abstract and concrete physics concepts. Additionally, its use is engaging and more interactive for students.